PRACTISING READING SKILLS IN TEACHING THE POEM “DONG CHI” [COMRADE] OF CHÍNH HỮU (9th GRADE LITERATURE, VOLUME 1) TO IMPROVE READING COMPREHENSION ABILITY FOR STUDENTS - Do Thi Lan (Vietnam Journal of Education, 2023)
Reading comprehension ability plays a very important role in solving academic as well as other problems in life. It is formed and developed from subjects such as Vietnamese (primary schools) and Literature (secondary and high schools). Improving reading comprehension ability in teaching the text is a topic in which many researchers have interest. In this study, we are addressing the issue of developing reading skills and enhancing teamwork in teaching the poem “Đồng chí” [Comrade] to develop reading comprehension ability in particular and other abilities for learners in general.